2018
DOI: 10.1111/bcp.13669
|View full text |Cite
|
Sign up to set email alerts
|

In vivo affinity and target engagement in skin and blood in a first‐time‐in‐human study of an anti‐oncostatin M monoclonal antibody

Abstract: AimsThe oncostatin M (OSM) pathway drives fibrosis, inflammation and vasculopathy, and is a potential therapeutic target for inflammatory and fibrotic diseases. The aim of this first‐time‐in‐human experimental medicine study was to assess the safety, tolerability, pharmacokinetics and target engagement of single subcutaneous doses of GSK2330811, an anti‐OSM monoclonal antibody, in healthy subjects.MethodsThis was a phase I, randomized, double‐blind, placebo‐controlled, single‐dose escalation, first‐time‐in‐hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Loss of OSM signaling may explain the severe congenital thrombocytopenia in A-II-2. Genetic ablation of either OSM (Sato et al, 2014) or OSM receptor (Tanaka et al, 2003) in mice is associated with thrombocytopenia, and a first-time-in-human study of an anti-OSM monoclonal antibody (GSK2330811) was associated with thrombocytopenia (Reid et al, 2018). Patient C-II-3 survived infancy and developed additional immunologic symptoms of eczematoid dermatitis reminiscent of defective IL-6/GP130/ STAT3 signaling, as observed in previous GP130 homozygous patients with missense variants in IL6ST (Schwerd et al, 2017;Shahin et al, 2019).…”
Section: Intronic Variant C1699+4a>g Gp130 Leads To Loss Of Functionmentioning
confidence: 59%
“…Loss of OSM signaling may explain the severe congenital thrombocytopenia in A-II-2. Genetic ablation of either OSM (Sato et al, 2014) or OSM receptor (Tanaka et al, 2003) in mice is associated with thrombocytopenia, and a first-time-in-human study of an anti-OSM monoclonal antibody (GSK2330811) was associated with thrombocytopenia (Reid et al, 2018). Patient C-II-3 survived infancy and developed additional immunologic symptoms of eczematoid dermatitis reminiscent of defective IL-6/GP130/ STAT3 signaling, as observed in previous GP130 homozygous patients with missense variants in IL6ST (Schwerd et al, 2017;Shahin et al, 2019).…”
Section: Intronic Variant C1699+4a>g Gp130 Leads To Loss Of Functionmentioning
confidence: 59%
“…A wider use has been demonstrated with inflammatory heart failure [ 430 ]. A trial with oncostatin M monoclonal antibody GSK2330811 has completed phase I (phase II ongoing) [ 431 ]. Therapeutic options for a more general anti-inflammatory use can still be conceptualized.…”
Section: Effects Predominantly or Exclusively On Sensory Neuronsmentioning
confidence: 99%
“…Interestingly, anti-OSM humanized antibodies have proven to be safe and well tolerated 19 and are now in Phase 2 clinical trials for the treatment of inflammatory diseases, such as systemic sclerosis and Crohn's disease. Together, our findings further strengthen the case for the preclinical investigation of OSM:OSMR blocking antibodies as a targeted anti-cancer therapy.…”
Section: Analysis Of Human Breast Cancer Samples Revealed That Our Rementioning
confidence: 99%
“…antibodies against OSM are being tested in clinical trials for the treatment of inflammatory diseases and have shown to be safe and well tolerated 19 .…”
Section: Introductionmentioning
confidence: 99%